Book Reviews (The Australian journal of anthropology, 2002)
Book reviewed in this article: A. Haroon Akram-Lodhi (ed.). Confronting Fiji Futures. Dwight B. Heath. Drinking Occasions: Comparative Perspectives on Alcohol and Culture. Alphonso Lingis, Dangerous Emotions. Chris Lyttleton. Endangered Relations: Negotiating Sex and AIDS in Thailand. Jeannette Marie Mageo (ed.). Cultural Memory: Reconfiguring History and Identity in the Postcolonial Pacific. Serena Nanda. Gender Diversity: A Crosscultural Perspective. Douglas Raybeck. Looking Down the Road: A Systems Approach to Future Studies. Tim Rowse. Obliged to be Difficult: Nugget Coombs' Legacy in Indigenous Affairs.